A Novel Corneal Remodeling Technique of Laser Asymmetric Keratectomy in Keratoconus Suspect: A Retrospective Case Control Study - Min JS; Min BM (Clinical Ophthalmology)
Ji Sang Min,1 Byung Moo Min2 1Department of Ophthalmology, The Institute of Vision Research, Yonsei University College of Medicine, Seoul, 03722, Republic of Korea; 2Woori Eye Clinic, Affiliated Clinical Professor to Department of Ophthalmology, Yonsei University College of Medicine, Daejon, 35229, Republic of KoreaCorrespondence: Byung Moo Min, Woori Eye Clinic, Affiliated Clinical Professor to Department of Ophthalmology, Yonsei University School of Medicine, Daeduk Daero 219 (Dunsan-dong), Seo-gu, Daejon, 35229, Republic of Korea, Tel +82-42-476-1675, Fax +82-42-476-1670, Email bmin8275@naver.comPurpose: This retrospective case control study report includes 4 eyes of 4 patients (aged from 37 to 44 years) with keratoconus suspect (KCS) who underwent laser epithelial keratomileusis linked laser asymmetric keratectomy (L-LAK) as corneal remodeling technique in order to avoid postoperative corneal ectasia.Patients and Methods: Four eyes of 4 patients showed corneal topography findings with abnormal localized steep keratometric curvature greater than 47.0 D and peripheral corneal thickness asymmetry (Total corneal central thickness deviations in four directions on Orbscan map (SUM)≥ 80 μm). L-LAK could be performed both the original ablation of refractive errors (SE from − 1.25 to − 5.50 D) and the customized ablation (selective ablation of the thicker peripheral cornea averaging:64 μm selectively and the central cornea of the myopic shift due to LAK averaging-1.50D. The main outcome measures between preoperative and postoperative 2 year were refraction, visual acuity (UDVA), keratometry, corneal symmetry evaluating SUM.Results: After 2 years, SEs (D, average) were − 0.34, UDVA (LogMAR) was 0.00. keratometry including Kmax was markedly decreased, SUM had diminished markedly. There were no case of postoperative adverse effects.Conclusion: L-LAK resulted in a decreased SUM, increased corneal symmetry, and no postoperative corneal ectasia with good visual outcomes in myopic patients with KCS.Keywords: keratoconus suspect, corneal remodeling, L-LAK, KCS, linked laser asymmetric keratectomy